Bionic Fluorine‐Free Multifunctional Photothermal Surface for Anti/de/Driving‐Icing and Droplet Manipulation - Lin Wang; Chengchun Zhang; Yasong Zhang; Chun Shen; Zhentao Xin; Zhenjiang Wei (Advanced Science)
Abstract Due to safety concerns associated with ice accumulation, there is a need to develop a durable surface with anti/de‐icing properties. Inspired by Gecko skin and Nepenthes, a superhydrophobic photothermal surface (SH‐PS) with micro‐nano hierarchical structure based on carbon nanotube composites is prepared by one‐step laser method. It can be switchable to a slippery photothermal surface (S‐PS) by injecting silicone oil. S‐PS can effectively delay icing at −20 °C/−30 °C, and maintain excellent dynamic anti‐icing capabilities following 28 times supercooled droplet impact (−30 °C). Under near‐infrared (NIR) irradiation, S‐PS exhibits high‐efficiency photothermal deicing and excellent ice droplet control capabilities. Furthermore, S‐PS also exhibits remarkable droplet manipulation capabilities under NIR irradiation, even anti‐gravity transport (8°) and programmable track manipulation. Notably, after 20 m abrasion, the S‐PS still maintains good performances of anti/de‐icing and droplet manipulation after infusing lubricant. All these excellent performances can promote its application in a wider range of fields.